A tale of two countries: Poverty among immigrants in Denmark and Sweden since 1984 - Kræn Blume; Björn Gustafsson; Peder J. Pedersen; Mette Verner (The United Nations University World Institute for Development Economics Research (UNU-WIDER), 2003)
The paper focuses on the problems of low income among immigrants, analysed by using comparable panel datasets for two Scandinavian welfare states. After a brief survey of a few earlier studies on immigrant poverty, we present Denmark and Sweden as interesting cases for comparative research. Cyclical profiles have been very different since the 1980s and both countries have experienced considerable differences with regard to the number and composition of immigrants from the less developed countries. Poverty rates, analysed relative to different background factors, are fairly high, in particular when considering the welfare state background of Denmark and Sweden. A number of differences are found in spite of the institutional similarities between the two countries. – poverty ; immigrant ; panel data
Keywords: D31; J15; J61; 330; Armut; Dänemark; Schweden; Migranten